Underlying mechanisms of retained placenta: Evidence from a population based cohort study. (September 2017) - Greenbaum, Shirley; Wainstock, Tamar; Dukler, Doron; Leron, Elad; Erez, Offer
Abstract: Objective: To determine risk factors for retained placenta, and to identify supporting epidemiologic evidence for the three previously-proposed mechanisms: (i) invasive placentation, (ii) placental hypo-perfusion, and (iii) inadequate uterine contractility. Design: A retrospective population-based cohort study. Setting and population: Israeli population in the southern district. Methods: Data were analyzed from a tertiary hospital database, between 1989 and 2014, using univariate tests and generalized estimating equation (GEE) multivariable models. Main outcome measures: Prevalence of retained placenta. Results: The study population included 205, 522 vaginal deliveries of which 4.8% (n = 9870) were complicated with retained placenta. Previous intra-uterine procedures and placenta-related pregnancy complications were found to be significant risk factors for retained placenta (history of cesarean section aOR = 8.82, 95%CI 8.35–9.31; history of curettage aOR = 12.80, 95%CI 10.57–15.50; pre-eclampsia aOR = 1.25, 95%CI 1.14–1.38; delivery of a small for gestational age neonate aOR = 1.08, 95%CI 1.01–1.16; stillbirth aOR = 2.34, 95%CI 1.98–2.77). During labour, the risk for retained placenta was increased in presence of arrest of dilatation (aOR = 2.03, 95%CI 1.08–3.82) or arrest of descent (aOR = 1.55, 95%CI 1.22–1.96). Infections of the uterine cavity during labour were also found to be strongly associated with increased risk of retained placenta (endometritis aOR = 2.21, 95%CI 1.64–2.97; chorioamnionitis aOR = 3.35, 95% CI 2.78–4.04). Conclusions: Supporting epidemiologic evidence were found for all three underlying mechanisms. In addition, there is evidence to suggest that intrauterine infection and inflammation may also be a possible pathology associated with retained placenta. Tweetable abstract: Risk factors for retained placenta support previously proposed mechanisms in a large cohort study